2019
DOI: 10.3389/fendo.2019.00534
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Sensitivity Is Not Decreased in Adult Patients With Hypopituitarism Without Growth Hormone Replacement

Abstract: Decreased insulin sensitivity in patients with hypopituitarism without GH replacement (pHP-WGHR) remains conflicting in literature. It is known that these patients present a decrease in free fat mass and an increase in fat mass. Typically, these kinds of alterations in body composition are associated with a decrease in insulin sensitivity; however, there is no consensus if this association is found in pHP-WGHR. Thus, we investigated pHP-WGHR regarding insulin sensitivity by euglycemic hyperinsulinemic clamp, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…In this sense, in a previous study, our group showed that, unlike what was observed in individuals with normal pituitary function, the agreement between the assessment of IS by the homeostatic model assessment for insulin resistance (HOMA-IR) and the euglycemic hyperinsulinemic clamp (EHC) was poor in patients with hypopituitarism [13]. This was also reported in another study where it is suggested that standard minimal homeostatic models to assess IS, such as HOMA-IR, could not adequately identify IS in syndromes of severe short stature [14].These findings highlighted the relevance of EHC in the investigation of IS, since the EHC does not suffer interference from the insulin counter-regulatory hormones, which are altered in patients with hypopituitarism [13]. On the other hand, the stage of the disease onset, childhood or adulthood, could influence IS in patients with GHD.…”
Section: Introductionmentioning
confidence: 75%
“…In this sense, in a previous study, our group showed that, unlike what was observed in individuals with normal pituitary function, the agreement between the assessment of IS by the homeostatic model assessment for insulin resistance (HOMA-IR) and the euglycemic hyperinsulinemic clamp (EHC) was poor in patients with hypopituitarism [13]. This was also reported in another study where it is suggested that standard minimal homeostatic models to assess IS, such as HOMA-IR, could not adequately identify IS in syndromes of severe short stature [14].These findings highlighted the relevance of EHC in the investigation of IS, since the EHC does not suffer interference from the insulin counter-regulatory hormones, which are altered in patients with hypopituitarism [13]. On the other hand, the stage of the disease onset, childhood or adulthood, could influence IS in patients with GHD.…”
Section: Introductionmentioning
confidence: 75%
“…As shown in Table 2, the literature is controversial regarding the results of IS in patients with GHD. Some studies show that these patients have insulin resistance (86)(87)(88)(89)(90) and others show that IS is similar to the gender, age and BMI matched controls (41,42,88,(90)(91)(92).…”
Section: Insulin Sensitivity In Ghdmentioning
confidence: 91%
“…It only evaluates insulin-dependent glucose uptake, faithfully representing the sensitivity to insulin action in these patients. In this regard, studies in humans have already demonstrated the lack of correlation between EHC and other methods used to assess IS in patients with GHD (41,42) suggesting that using other methods may induce controversial results. Therefore, in this review we considered only scientific studies that used HEC as a method for assessing IS in patients with GHD.…”
Section: Insulin Sensitivity Assessment Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent metaanalyses involving observational studies have confirmed such increased mortality, with higher rates observed especially in women and in patients of younger age at diagnosis (5,6). Nevertheless, new concepts in the pathophysiology of hormonal deficiencies, recent advances in diagnostic tools, and the emergence of new formulations for hormone replacement have significantly contributed to a reduction in morbidity and mortality rates in these patients (7)(8)(9)(10). This narrative review provides a guide for the management of patients with hypopituitarism in Brazil, considering as much as possible regional differences and health care disparities.…”
Section: Introductionmentioning
confidence: 99%